Interpersonal trauma and mental health problems of male and female antisocial adolescents treated in a forensic outpatient setting. Issue 1 (2nd January 2020) - Slotboom, Anne-Marie; Hendriks, Jan; Hoeve, Machteld; Zahn, Margaret
ABSTRACT: The aim of the study was to examine whether the impact of interpersonal traumas on internalizing problems in antisocial adolescents treated in a community based forensic setting was moderated by gender. Data were collected in the Netherlands from a random sample of the available treatment files of 397 adolescents (200 males and 197 females) aged 12–18 years. Adolescent females more often experienced physical and sexual abuse, and internalizing symptoms and disorders than their male counterparts. Multiple regression analysis revealed that physical abuse, gender and ethnicity significantly predicted internalizing symptoms. A gender-physical abuse interaction effect was also found. In contrast to the hypothesis, physically abused males had a higher chance of developing internalizing symptoms than physically abused females. Sexual abuse was associated with internalizing disorders (mainly dysthymia and PTSD) for both males and females. Although the literature suggests that the link between traumatic experiences and mental health problems is stronger for females than for males, we did not find evidence for this in our forensic outpatient sample of antisocial adolescents.